Heat transfer study of submicro-encapsulated PCM plate for food packaging application. (April 2015) - Hoang, H.M.; Leducq, D.; Pérez-Masia, R.; Lagaron, J.M.; Gogou, E.; Taoukis, P.; Alvarez, G.
Abstract: In recent studies, encapsulated phase change materials (PCM) were developed as novel materials for food packaging because of their improved thermal insulation capacity. The PCMs (often liquid in room temperature) are encapsulated in a shell material so as they can be practically handled. In this work, the thermal behaviour of an encapsulated PCM material (Rubitherm RT5 encapsulated in polycaprolactone PCL) with two different PCM mass fractions was studied. The model was validated by experimental cooling and heating processes, under controlled air temperature conditions. The numerical result demonstrated a better thermal buffering capacity of the encapsulated PCM material compared to a standard one (cardboard). Highlights: Submicro – encapsulated PCM were developed as novel materials for food packaging. The material has a better thermal buffering capacity compared to a standard one. Using this material allows increasing the product shelf-life.